Media Video Animasi Jerman dalam Meningkatkan Kemampuan Menyimak - Fatmawati Hasan; Syamsu Rijal; Hasmawati Hasmawati (Universitas Negeri Makassar, 2023)
Abstract. This research is a classroom action research which consists of two cycles. Each cycle consists of planning, implementing, observing and reflecting. The purpose of this study was to improve the listening skills of class XI IPS students at SMA Negeri 3 Sinjai. The data in this study consists of two types, namely: quantitative data and qualitative data. Qualitative data were obtained through observation and quantitative data obtained through the results of the listening ability test cycle I and cycle II. The results of the data analysis showed that the value of listening skills obtained by students in the first cycle was 67.3% while in the second cycle it was 86.53%. These results indicate that the use of German animated video media can improve the listening skills of class XI IPS students at SMA Negeri 3 Sinjai.Keywords: Listening Skills, Animated Videos, Classroom Action Research